2015
DOI: 10.15406/unoaj.2015.02.00021
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Gastrointestinal Bleeding in DialysisPatients:Five Years' Experience in a Single Dialysis Center

Abstract: Background and study aims: Dialysis patients can develop a number of gastrointestinal (GI) lesions that can result in bleeding in emergency situations. Our aim was to investigate the nature of GI bleeding that needed emergency endoscopy. Patients and Methods: Over a 5-year period (April 1, 2007-March 31, 2012), we studied consecutive dialysis patients with GI bleeding who underwent emergency endoscopic procedures. Demographic and clinical data were also collected. Results: Fifty-two patients were hospitalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…14 Yorioka et al, 15 reported on a patient with end-stage renal disease (ESRD) and bleeding from watermelon stomach (gastric antral vascular ectasia) who improved after the dialysis modality was changed from HD to CAPD. However, other reports exist of watermelon stomach and bleeding in CAPD patients 16,17 which may counter the suggestion of haemostatic risk factors, except uremic toxins, contributing to the occurrence of watermelon stomach in CAPD patients. In the present study, two CAPD patients with upper GI bleeding and one CAPD patient with lower GI bleeding were diagnosed as having gastric antral vascular ectasia.…”
Section: Discussionmentioning
confidence: 92%
“…14 Yorioka et al, 15 reported on a patient with end-stage renal disease (ESRD) and bleeding from watermelon stomach (gastric antral vascular ectasia) who improved after the dialysis modality was changed from HD to CAPD. However, other reports exist of watermelon stomach and bleeding in CAPD patients 16,17 which may counter the suggestion of haemostatic risk factors, except uremic toxins, contributing to the occurrence of watermelon stomach in CAPD patients. In the present study, two CAPD patients with upper GI bleeding and one CAPD patient with lower GI bleeding were diagnosed as having gastric antral vascular ectasia.…”
Section: Discussionmentioning
confidence: 92%
“…Higher rate of angiodysplasia was shown in patients on hemodialysis than in those on peritoneal dialysis (7). Gastric antral vascular ectasia was documented as the most common cause of UGI bleeding as well as recurrent bleeding in patients who received dialysis therapy during emergencies, followed by gastroduodenal ulcer disease (34,39).…”
Section: Causes Of Ugi Bleedingmentioning
confidence: 99%
“…In ESRD patients, the estimated frequency is 21 bleeds per 1,000 patient years with a very high risk of mortality accounting for 3-7% of all deaths (7,8,32,33). Disordered hemostasis of uremia resulting from platelet and endothelial dysfunction, associated anemia, secondary hyperparathyroidism and the use of medications that likely affect the clotting cascade (e.g., clopidogrel, aspirin, and other NSAIDs) are considered risk factors for UGI bleeding (2,9,32,34).…”
Section: Upper Gastrointestinal Bleedingmentioning
confidence: 99%
See 1 more Smart Citation